Deep Carbon Cycling Over the Past 200 Million Years: A Review of Fluxes in Different Tectonic Settings - Wong, Kevin; Mason, Emily; Brune, Sascha; East, Madison; Edmonds, Marie; Zahirovic, Sabin (Frontiers in Earth Science, 2019)
Carbon is a key control on the surface chemistry and climate of Earth. Significant volumes of carbon are input to the oceans and atmosphere from deep Earth in the form of degassed CO2 and are returned to large carbon reservoirs in the mantle via subduction or burial. Different tectonic settings (e.g. volcanic arcs, mid-ocean ridges, and continental rifts) emit fluxes of CO2 that are temporally and spatially variable, and together they represent a first-order control on carbon outgassing from the deep Earth. Changes in the relative importance of different tectonic settings throughout Earth's history has therefore played a key role in balancing the deep carbon cycle on geological timescales. Over the past ten years the Deep Carbon Observatory has made enormous progress in constraining estimates of carbon outgassing flux at different tectonic settings. Using plate boundary evolution modelling and our understanding of present-day carbon fluxes, we develop time series of carbon fluxes into and out of the Earth’s interior through the past 200 million years. We highlight the increasing importance of carbonate-intersecting subduction zones over time to carbon outgassing, and the possible dominance of carbon outgassing at continental rift zones, which leads to maxima in outgassing at 130 and 15 Ma. To a first-order, carbon outgassing since 200 Ma may be net positive, averaging ~50 Mt C yr-1 more than the ingassing flux at subduction zones. Our net outgassing curve is poorly correlated with atmospheric CO2, implying that surface carbon cycling processes play a significant role in modulating carbon concentrations and/or there is a long-term crustal or lithospheric storage of carbon which modulates the outgassing flux. Our results highlight the large uncertainties that exist in reconstructing the corresponding in- and outgassing fluxes of carbon. Our synthesis summarizes our current understanding of fluxes at tectonic settings and their influence on atmospheric CO2, and provides a framework for future research into Earth’s deep carbon cycling, both today and in the past.